Short Communication: Metabolic Syndrome and Adaptogenic Nutritional Supplement “AdMax” - Antoshechkin, A.G. (Journal of Nutritional Therapeutics, 2016)
Metabolic syndrome manifestations include chronic fatigue, insulin resistance, elevated levels of glucose, lipids and cholesterol in the blood, and overweight. The main targets of nutritional supplement “AdMax” are the activation of energy metabolism and stress counteraction. In addition, the “AdMax” constituents decrease the concentration of blood glucose, enhance glucose utilization by cells, decrease the activity of triglyceride lipase and lower blood cholesterol levels. Comparison of metabolic syndrome manifestations to the activities of “AdMax” constituents argues that “AdMax” can be used as a preventive and treatment remedy for metabolic syndrome.